2001
DOI: 10.1111/1467-8683.00254
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Intellectual Capital: some conceptualisations

Abstract: One of the persistent problems facing corporate governance is the increasing shift toward knowledge-intensive organisations. This article focuses on the fiduciary responsibility of corporate governance for creating, developing, and leveraging the intellectual capital existing and embedded in the people, structures, and processes of the firm. Research and practice, traditionally concerned with governance responsibility for financial and physical capitals, has not much focused on the relations between governance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
166
0
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(190 citation statements)
references
References 25 publications
13
166
0
11
Order By: Relevance
“…Such disclosure reduces risk perception among investors by facilitating a more accurate estimation of future earnings (Keenan and Aggestam, 2001;Van der Meer-Kooistra and Zijlstra, 2001;Li, Pike, and Haniffa, 2008). Barako, Hancock, and Izan (2006) examined the corporate disclosure of Kenyan listed firms and the effect of corporate governance and ownership characteristics.…”
Section: Relevant Literaturementioning
confidence: 99%
“…Such disclosure reduces risk perception among investors by facilitating a more accurate estimation of future earnings (Keenan and Aggestam, 2001;Van der Meer-Kooistra and Zijlstra, 2001;Li, Pike, and Haniffa, 2008). Barako, Hancock, and Izan (2006) examined the corporate disclosure of Kenyan listed firms and the effect of corporate governance and ownership characteristics.…”
Section: Relevant Literaturementioning
confidence: 99%
“…Corporate governance served as mechanisms that assist firms to achieve their objectives while disclosure is an essential tool for reporting their corporate performance to investors. Keenan and Aggestam (2001), Li et al, (2008), Clemente and Labat (2009) and Akhtaruddin et al, (2009) argued that effective corporate governance mechanisms have impacts on efficient intellectual capital management, including the disclosure of information to stakeholders. The investors are to be informed about the core strengths of the company when it disclosed its intellectual capital owned (Kavida and Sivakoumar, 2008), thus, promoting the transparency.…”
Section: Corporate Governance and Disclosure Environment In Malaysiamentioning
confidence: 99%
“…Adoption of internal control devices, such as audit committees and non-executive directors, and separation of the roles of chairman and chief executive, may enhance monitoring quality in critical decisions about intellectual capital investment and performance (Keenan and Aggestam, 2001). However, our study found that no significant relationship between such internal control devices with the voluntary intellectual capital disclosure.…”
Section: Concluding Commentsmentioning
confidence: 99%
“…Considerando que os investidores procuram informações sobre os negócios da organização que são relevantes para a tomada de decisão, a evidenciação do capital intelectual nos relatórios anuais pode reduzir a percepção de risco e permitir uma estimação de ganhos futuros mais acurada (KEENAN; AGGESTAM, 2001). Dessa forma, a evidenciação do capital intelectual pode interferir na captação de novos investidores e na capacidade de decisão dos gestores nas corporações.…”
Section: Introductionunclassified